Cannabidiol Ameliorates Doxorubicin-Induced Myocardial Injury via Activating Hippo Pathway - Dong T; Li J; Liang X; Wang W; Chen M; Yang G; Wu D (Drug Design, Development and Therapy)
Tianwei Dong,1 Jinlian Li,2 Xinfang Liang,3 Wang Wang,3 Meichi Chen,4 Guangyuan Yang,5 Dongmei Wu4 1Key Laboratory of Microecology-Immune Regulatory Network and Related Diseases, School of Basic Medicine, Jiamusi University, Jiamusi, Heilongjiang, 154000, People’s Republic of China; 2College of Pharmacy, Jiamusi University, Jiamusi, Heilongjiang, 154007, People’s Republic of China; 3Department of Cardiology, The First Affiliated Hospital of Jiamusi University, Jiamusi, Heilongjiang, 154002, People’s Republic of China; 4School of Basic Medicine, Jiamusi University, Jiamusi, Heilongjiang, 154000, People’s Republic of China; 5Cardiovascular Medicine, The First Affiliated Hospital of Jiamusi University, Jiamusi, Heilongjiang, 154002, People’s Republic of ChinaCorrespondence: Dongmei Wu; Guangyuan Yang, Email dmwu@jmsu.edu.cn; Ygy665@126.comBackground: Doxorubicin (DOX) is a chemotherapeutic agent widely used for cancer treatment and has non-negligible cardiotoxicity. Some previous studies have reported that cannabidiol (CBD) has cardioprotective effects. In this study, we evaluated the protective effects of CBD against DOX-induced cardiomyocyte injury, and explored the downstream molecular mechanism.Methods and Materials: GSE193861, containing healthy myocardial tissues and myocardial tissues with DOX-induced injury, was analyzed to screen for the involved proteins and pathways. Molecular docking was performed to identify candidate drugs. After H9c2 cells were treated with DOX and CBD, their viability, oxidative stress, and apoptosis were assessed. After YAP depletion, the role of the Hippo pathway in CBD function was investigated. C57BL/6 mice were treated with DOX to establish an in vivo model, and CBD and verteporfin (VP) were used to treat the mice. Histological analyses and immunofluorescence were used to evaluate myocardial tissue injury, and apoptosis and oxidative stress of the myocardial tissues were also analyzed. Western blotting was used to investigate the regulatory effects of CBD on the Hippo and apoptosis-related pathways.Results: Bioinformatic analysis suggested that the Hippo pathway was a crucial pathway involved in DOX-induced myocardial injury. Molecular docking showed that CBD targeted multiple regulators of the Hippo pathway. CBD showed cardioprotective effects against DOX-induced myocardial injury both in vitro and in vivo and regulated Hippo pathway activity in cardiomyocytes. After inactivation of the Hippo pathway by YAP knockdown or VP intervention, the protective effects of CBD were reversed.Conclusion: For the first time, we revealed that CBD is likely to reduce DOX-induced myocardial injury by regulating the Hippo signaling pathway.Keywords: doxorubicin, heart injury, cannabidiol, Hippo pathway